2022
DOI: 10.3390/genes13020192
|View full text |Cite
|
Sign up to set email alerts
|

The SLC27A1 Gene and Its Enriched PPAR Pathway Are Involved in the Regulation of Flavor Compound Hexanal Content in Chinese Native Chickens

Abstract: The role of hexanal in flavor as an indicator of the degree of oxidation of meat products is undeniable. However, the genes and pathways of hexanal formation have not been characterized in detail. In this study, we performed differential gene expression analysis and weighted gene co-expression network analysis (WGCNA) on groups of Tiannong partridge chickens with different relative hexanal content in order to find the genes involved in the formation of hexanal and the specific pathways of hexanal formation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Our previous study in Tiannong Partridge chickens showed that the differentially expressed genes between the high and low hexanal content groups were significantly enriched in the PPAR signaling pathway, glycerophospholipid metabolism, MAPK signaling pathway, fatty acid biosynthesis, fatty acid degradation, etc. (Jin et al, 2022). In this study, hexanal candidate genes were also involved in multiple fatty acid and amino acid related pathways, and lipid related GO terms.…”
Section: Discussionmentioning
confidence: 62%
“…Our previous study in Tiannong Partridge chickens showed that the differentially expressed genes between the high and low hexanal content groups were significantly enriched in the PPAR signaling pathway, glycerophospholipid metabolism, MAPK signaling pathway, fatty acid biosynthesis, fatty acid degradation, etc. (Jin et al, 2022). In this study, hexanal candidate genes were also involved in multiple fatty acid and amino acid related pathways, and lipid related GO terms.…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, it is worth noting that free-range chickens like Lueyang black chickens tend to have higher hexanal content compared to cage-raised chickens—a factor that may contribute to their unique aroma profile [ 39 ]. Research has also shown a close relationship between SLC27A1 gene expression and peroxisome proliferator-activated receptor (PPAR) pathway activation with hexal content in Chinese local chicken VOCs [ 40 ]. Yuan et al [ 41 ] identified 16 candidate genes related to fatty acid pathways while highlighting a significant association between polyunsaturated fatty acids (PUFAs) and both aldehyde content as well as hexanal content within Chinese local chickens.…”
Section: Resultsmentioning
confidence: 99%
“…Lueyang black chicken is a kind of free-range chicken in mountainous areas, and the hexanal content of free-range chickens is greater than that of cage-range chickens [36], and this may be one of the reasons for the high hexanal content of Lueyang black chicken breast meat. Research also showed that the SLC27A1 gene and peroxisome proliferator-activated receptor (PPAR) pathway are closely related to hexal content in Chinese local chicken VOCs [37].…”
Section: Qualitative Analysis Of Vocs In Four Chicken Breastmentioning
confidence: 99%